Lipase‐Catalyzed Kinetic Resolution of (±)‐1‐(2‐Furyl) Ethanol in Nonaqueous Media. Issue 6 (15th April 2014) - Devendran, Saravanan; Yadav, Ganapati D.
ABSTRACT S‐1‐(2‐Furyl) ethanol serves as an important chiral building block for the preparation of various natural products, fine chemicals, and is widely used in the chemical and pharmaceutical industries. In this work, lipase‐catalyzed kinetic resolution of (R/S)‐1‐(2‐furyl) ethanol using different acyl donors was investigated. Vinyl esters are good acyl donors vis‐à‐vis alkyl esters for kinetic resolution. Among them, vinyl acetate was found to be the best acyl donor. Different immobilized lipases such as Rhizomucor miehei lipase, Thermomyces lanuginosus lipase, and Candida antarctica lipase B were evaluated for this reaction, among which C. antarctica lipase B, immobilized on acrylic resin (Novozym 435), was found to be the best catalyst in n‐heptane as solvent. The effect of various parameters was studied in a systematic manner. Maximum conversion of 47% and enantiomeric excess of the substrate (ees) of 89% were obtained in 2 h using 5 mg of enzyme loading with an equimolar ratio of alcohol to vinyl acetate at 60°C at a speed of 300 rpm in a batch reactor. From the analysis of progress curve and initial rate data, it was concluded that the reaction followed the ordered bi–bi mechanism with dead‐end ester inhibition. Kinetic parameters were obtained by using nonlinear regression. This process is more economical, green, and easily scalable than the chemical processes. Chirality 26:286–292, 2014. © 2014 Wiley Periodicals, Inc.